Designing a control system Based on SOC Estimation of BMS for PV-Solar System - Buswig, Yonis M. Yonis; Qays, Ohirul; Affam, Azuka; Albalawi, Hani; Othman, Al-Khalid; Julai, Norhuzaimin; Yi, Sim Sy (International Journal of Integrated Engineering, 2020)
One of the major challenges for battery energy stowage system is to design a supervisory controller which can yield high energy concentration, reduced self-discharge rate and prolong the battery lifetime. A regulatory PV-Battery Management System (BMS) based State of Charge (SOC) estimation is presented in this paper that optimally addresses the issues. The proposed control algorithm estimates SOC by Backpropagation Neural Network (BPNN) scheme and utilizes the Maximum Power Point Tracking (MPPT) scheme of the solar panels to take decision for charging, discharging or islanding mode of the Lead-Acid battery bank. A case study (SOC estimation) is demonstrated as well to depict the eï¬€iciency (Error 0.082%) of the proposed model using real time data. The numerical simulation structured through real-time information concedes that the projected control mechanism is robust and accomplishes several objectives of integrated PV-BMS for instance avoiding overcharging and deep discharging manner under diï¬€erent solar radiations.